Land management in Chile: state of the art - Márquez Poblete, Marco Aurelio; Veloso Pérez, Eva (Estado, Gobierno y Gestión Pública, 2021)
For more than two decades, the various disciplines linked to the study of the territory have been reflecting on and theorizing about land use, and itsusefulness in the proper use of geographic space and its potential as a tool to achieve the equitable and sustainable development of quality of life. of the country’s inhabitants.From the State level, the authorities, experts in public policies and the various public services that have competence in matters of planning andmanagement of the territory also demand the use of land use as a tool to face the growing conflicts regarding land use.The territorial impacts generated by the social crisis of October 2019 and the covid-19 pandemic urgently demand a new management of human settlements in the country, in which land use planning can be an effective tool. The objective of this work is to conceptualize in the light of the reflection of the last decades, which is understood by territorial ordering, to explain what are its methodological foundations, to review in the Chilean case the existing legal framework in the matter and the applications that have been carried out on this theme.